The Women of Mexico's Cultural Renaissance
VIII, 205 p. 1 illus. in color.
Keywords: This delightful collection of essays by Elena Poniatowska presents readers with a wide panorama of important Mexican female artists and writers. Elizabeth Martínez’s excellent translation brings Poniatowska’s keen eye and searing observations beautifully into English, meaning that these extraordinary women, their lives, and their art emerge fully realized from the page. The book is a wonderful read for both those well-versed in Mexican literature and for those wanting to know more about Mexican art and culture! - Paul M. Worley and Melissa Birkhofer, Appalachian State University, North Carolina, translators of Word Mingas: Oralitegraphies and Mirrored Visions on Oralitures and Indigenous Contemporary Literatures by Miguel Rocha Vivas This book consists of a collection of essays by Mexican writer Elena Poniatowska in their first English translation, and a critical introduction. The highly engaging essays explore the lives of seven transformational figures for Mexican feminism. This includes Frida Kahlo, Maria Izquierdo, and Nahui Olin, three outstanding artists of the cultural renaissance of the early twentieth century, and Nellie Campobello, Elena Garro, Rosario Castellanos, and Pita Amor, forerunner writers and poets whose works laid a path for Mexican women writers in the later twentieth century. Poniatowska’s essays discuss their fervent activity, interactions with other prominent figures, details and intricacies about their specific works, their scandalous and irreverent activities to draw attention to their craft, and specific revelations about their lives. The extensive critical introduction surveys the early feminist movement and Mexican cultural history, explores how Mexico became a more closed society by the mid-twentieth century, and suggests further reading and films. This book will be of interest both to the general reader and to scholars interested in feminist/gender studies, Mexican literary and cultural studies, Latin American women writers, the cultural renaissance, translation, and film studies. Elizabeth Coonrod Martinez was Professor at DePaul University, USA, 2010 to 2020, and at Sonoma State University, USA, 1995 to 2010. Her recent books include Teaching Late Twentieth Century Mexicana and Chicana Writers (2021), Josefina Niggli, Mexican American Writer: A Critical Biography (2007), and Lilus Kikus and Other Stories by Elena Poniatowska, translation and introduction (2005). She was Editor of the academic journal Diálogo, an Interdisciplinary Studies journal from 2010 to 2020. Elena Poniatowska is one of the most powerful and important voices of Spanish American literature and journalism. Her chosen genre is literary journalism, much of which is collected in the 7 volume Todo México (1991-1999). Her prolific career has won her many awards including the Mazatlán Prize twicefor Hasta no verte Jesús mío (1970) and Tinísima (1992), the Alfaguara Prize for La piel del cielo (2007), and the Cervantes Prize for Literature in 2013. .